2016
DOI: 10.5301/ejo.5000859
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Collagen Matrix Implantation in Infantile Glaucoma

Abstract: The short-term preliminary results of this study indicate that the combined trabeculotomy and trabeculectomy with Ologen implantation could potentially provide a safe and effective procedure in the infantile age group but longer duration of follow-up in larger number of patients is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In an approach similar to ours, Elhefney et al [13] studied ologen with combined trabeculotomy and trabeculectomy in infantile glaucoma and concluded that it could be safe and effective in the infantile age group but a longer follow-up in a larger number of patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In an approach similar to ours, Elhefney et al [13] studied ologen with combined trabeculotomy and trabeculectomy in infantile glaucoma and concluded that it could be safe and effective in the infantile age group but a longer follow-up in a larger number of patients is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although ologen application is safe, another study has reported that it does not result in a significant difference in controlling IOP and surgical success rate compared to the conventional AGV groups in humans 9 . In our study, we used ologen for AGV surgery to reduce bleb fibrosis.…”
Section: Discussionmentioning
confidence: 90%
“…Adequate IOP and vision were preserved in this cat for 5 years, without any systemic and topical medications 8 . The biodegradable collagen matrix is placed over the drainage device implant, and influences healing by causing fibroblasts and myofibroblasts to ingress into the pores and secrete connective tissue, thus forming a loose matrix 9 . Although the safety and efficacy of ologen during AGV implantation for human ophthalmological conditions remains controversial, we hypothesized that ologen may decrease the complications associated with MMC and 5‐FU among dogs 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Another was about congenital glaucoma showed that Ologen had equally effective results as MMC, and Ologen implantation is safe and has low incidences of complications [28] . The studies of Singab AAS and Elhefney EM showed that Ologen is a safe and effective adjuvant in combined trabeculotomy and trabeculectomy for treatment of Congenital glaucoma [24,45] . This may suggest that we should consider giving priority to Ologen in infants and adolescents, but more researches are needed to confirm our ideas.…”
Section: Discussionmentioning
confidence: 99%